Effects of plyometric training on lower body muscle architecture, tendon structure, stiffness and physical performance: A systematic review and meta-analysis - Ramírez-delaCruz, M.; Bravo-Sánchez, A.; Esteban-García, P.; Jiménez, F.; Abián-Vicén, J. (Sports Medicine - Open, 2022)
Background Plyometric training (PT) has been widely studied in sport science. However, there is no review that determines the impact of PT on the structural variables and mechanical properties of the lower limbs and physical performance.